Quantum mechanics - McMurry, Sara M. (Addison: Wesley Pub, 1993)
Provides an introduction to the theoretical foundations of quantum mechanics for students of experimental physics. It is intended as an intermediate text for those who have already completed an introductory course in quantum mechanics.
Includes bibliographical references; Appendix A-C, 349-368p.; Index 369-374p.
Keywords: Quantum Mechanics; Physics